Can Health/Medical Informatics be Regarded as a Separate Discipline? - Protti, D. J.; van Bemmel, J. H.; Gunzenhäuser, R.; Haux, R.; Warner, H.; Douglas, J. V.; Lang, E. (Methods of Information in Medicine, 1994)
The participants of the panel on education and training in Medical Informatics, concurred that health/medical informatics is today thriving as a separate discipline, despite inevitable uncertainties regarding the future. Conferees discussed the distinctions between physician-built systems and those designed by medical informaticians, focusing on methodology as critical to medical informatics.
Keywords: Medical Informatics; Health Informatics; Education; Training